HUBUNGAN POLA MAKAN DAN KEBIASAAN SARAPAN TERHADAP STATUS GIZI PEDAGANG PASAR PURWODADI KABUPATEN PURWOREJO - Hermayanti, Putri Mely; Pambudi, Brevi Istu (Jurnal Andaliman: Jurnal Gizi Pangan, Klinik dan Masyarakat, 2023)
Market traders are a group of workers who are prone to nutritional problems. Breakfast (breakfast) provides energy used for the first hour of activity including work. Nutrient intake is something that will affect their nutritional status. This study aims to analyze the relationship between eating patterns and breakfast habits with the nutritional status of traders in Purwodadi market, Purworejo district. This study used a cross-sectional research design located at Pasar Purwodadi, Purworejo Regency during July 2023. A total of 73 traders were collected for data on eating patterns using semi FFQ questionnaire. While nutritional status data was taken using anthropometric measurements in the form of height and weight. Analysis of the data used is the Spearman Rank correlation test. Most traders have normal nutritional status (58.9%), with breakfast habits in a fairly good category (54.8%) and a fairly good diet (97.3%). Based on the results of the Spearman rank correlation test, a positive and significant relationship was found between breakfast habits and nutritional status with p=0.035 (p<0.05), while traders' diets were not significantly related to nutritional status with p=0.276 (p> 0.05). Breakfast habits, especially in the morning, are related to the nutritional status of traders at the Purwodadi market, Purworejo district.Keywords—Breakfast, Market traders, FFQ